Formation Pathways and Emission Characteristics of PCDD/Fs during Co-combustion Tests of Sewage Sludge in Coal-fired Power Plants - Xiangbo Zou; Ji Ye; Chuangting Chen; Hui Huang; Wenxin Yu; Yuxuan Ying; Tieying Mao; Yunfeng Ma; Bingjian Zhu; Xiaoqing Lin (Aerosol and Air Quality Research)
Abstract This study was conducted in a full-scale coal-fired power plant (350 MW), mainly investigating the co-combustion influence of sewage sludge (SS) on the formation and emission characteristics of polychlorinated dibenzo-p-dioxins and dibenzofurans (PCDD/Fs). The introduction of SS enhanced the formation of major air pollutants such as NOx, SO2, and dust, but their emission concentrations still met the ultra-low emission requirements. By adding 3% and 6% SS, the formation concentrations of PCDD/Fs in flue gas at the economizer increased from 0.1317 to 0.2651 and 0.6023 ng m−3, respectively, and the corresponding I-TEQ concentrations increased from 0.0104 to 0.023 and 0.058 ng I-TEQ m−3, respectively. The emission concentrations of PCDD/F were steadily reduced to 0.0347–0.0645 ng Nm−3 (0.0021–0.0034 ng I-TEQ Nm−3) at the stack outlet. In comparison, the increased co-combustion ratio of SS decreased the 2,3,7,8-PCDD/F concentrations from 0.0222 to 0.0197–0.0098 ng g−1 and caused the change of dominant component from PCDDs (72.8%) to PCDFs (57.4%–59.5%) due to the inhibition effect of S-based substances. During the co-combustion process, de novo synthesis was confirmed as the major formation route of PCDD/Fs. Cu and Cl in mixed fuel of coal and SS were highly correlated with the parameters related to PCDD/Fs during co-combustion, which should be strictly limited to prevent large regeneration amounts of PCDD/Fs during the co-combustion process. The results provide an essential reference for controlling PCDD/F formation in the co-combustion process of SS and coal.